Improving Health in Adolescents About Healthy Reproduction at Senior High School 22 Maluku - Nanlohy, Wildia; Bugis, Nova; Nurhidayati, Siti; Thalib, Abdul (Journal of Evidence-Based Community Health, 2024)
Adolescent reproductive health issues are a serious global concern. Research findings show a significant increase in community service participants' knowledge after the intervention, indicating the positive impact of the program on their understanding of reproductive health. The improvement in knowledge may be attributed to effective educational methods employed during the intervention. Participant involvement in activities also played a crucial role in enhancing their understanding. However, it is essential to recognize that knowledge alone is insufficient to change behavior. Therefore, future interventions should focus on integrating components such as attitude change, social norms, and family/community involvement to achieve broader and sustainable impacts on adolescent reproductive health.